Advances in botanical research . - Delseny, Michel; Kader, Jean-Claude (Academic Press, 2008)
Presents reviews on a wide range of topics in plant sciences. This title features a wide range of reviews by recognized experts on various aspects of plant genetics, biochemistry, cell biology, molecular biology, physiology and ecology. It features six reviews on topics of interest to post-graduates and researchers alike.